Impact of soft magnetic material on design of high speed permanent magnet machines - Fernando, Nuwantha; Vakil, Gaurang; Arumugam, Puvaneswaran; Amankwah, Emmanuel K.; Gerada, C.; Bozhko, Serhiy (Institute of Electrical and Electronics Engineers, 2016)
This paper investigates the effect of two soft magnetic materials on a high speed machine design, namely 6.5% Silicon Steel and Cobalt-Iron alloy. The effect of design parameters on the machine performance as an aircraft starter-generator is analysed. The material properties which include B-H characteristics and the losses are obtained at different frequencies under an experiment and used to predict the machine performance accurately. In the investigation presented in this paper, it is shown that machines designed with 6.5% Silicon Steel at a high core flux density has lower weight and lower losses than the Cobalt-Iron alloy designs. This is mainly due to the extra weight contributed by the copper content especially in the end-windings. Due to the high operating frequencies, the core-losses in the Cobalt-Iron machine designs are found to outweigh the copper-losses incurred in the Silicon Steel machines. It is also shown that change in stack length/number of turns has a considerable effect on the copper losses at starting, however has no significant advantage on rated efficiency which happens to be in a field-weakening operating point. It is also shown that the performance of the machine designs depend significantly on material selection and the operating point of the core. The implications of the variation of design parameters on the machine performance is discussed and provides insight into the influence of parameters that effect overall power density.